101k views
15 votes
Solve the system of linear equations using the Gauss-Jordan elimination method.

2x + y − 2z = −3
x + 3y − z = −4
3x + 4y − z = 5
(x, y, z) =

1 Answer

7 votes

Answer:

x = -0.6

y = 2.2

z = 2

Explanation:

2x + y - 2z = -3

x + 3y - z = 4

3x + 4y - z = 5

Rewrite the system in matrix form and solve it by Gaussian Elimination (Gauss-Jordan elimination)

2 1 -2 -3

1 3 -1 4

3 4 -1 5

R1 / 2 → R1 (divide the 1 row by 2)

1 0.5 -1 -1.5

1 3 -1 4

3 4 -1 5

R2 - 1 R1 → R2 (multiply 1 row by 1 and subtract it from 2 row); R3 - 3 R1 → R3 (multiply 1 row by 3 and subtract it from 3 row)

1 0.5 -1 -1.5

0 2.5 0 5.5

0 2.5 2 9.5

R2 / 2.5 → R2 (divide the 2 row by 2.5)

1 0.5 -1 -1.5

0 1 0 2.2

0 2.5 2 9.5

R1 - 0.5 R2 → R1 (multiply 2 row by 0.5 and subtract it from 1 row); R3 - 2.5 R2 → R3 (multiply 2 row by 2.5 and subtract it from 3 row)

1 0 -1 -2.6

0 1 0 2.2

0 0 2 4

R3 / 2 → R3 (divide the 3 row by 2)

1 0 -1 -2.6

0 1 0 2.2

0 0 1 2

R1 + 1 R3 → R1 (multiply 3 row by 1 and add it to 1 row)

1 0 0 -0.6

0 1 0 2.2

0 0 1 2

x = -0.6

y = 2.2

z = 2

User Gokul
by
5.1k points